2009
DOI: 10.1590/s0103-05822009000100011
|View full text |Cite
|
Sign up to set email alerts
|

Anemia em crianças de uma creche pública e as repercussões sobre o desenvolvimento de linguagem

Abstract: OBJETIVO: Comparar o desenvolvimento de linguagem de crianças anêmicas e não-anêmicas de uma creche pública de Belo Horizonte. MÉTODOS: Estudo transversal com avaliação do desenvolvimento de linguagem de crianças anêmicas (casos) e não-anêmicas (controles) entre dois e seis anos de idade. Todas as crianças realizaram punção digital para detecção da anemia (hemoglobina <11,3g/dL). O Grupo Caso foi constituído por 22 crianças anêmicas e o Controle, por 44 crianças, selecionadas por amostragem aleatória paread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
19

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
(51 reference statements)
0
11
0
19
Order By: Relevance
“…A questão das mães estarem desempregadas pode refletir na condição sócio-econômica da famí-lia, favorecendo um pior estímulo ao desenvolvimento das crianças. Tais associações foram diferentes com aquelas da maioria das pesquisas, onde as principais associações são: baixa renda familiar, baixa escolaridade materna e maior número de irmãos 23,24,27 .…”
Section: Discussionunclassified
“…A questão das mães estarem desempregadas pode refletir na condição sócio-econômica da famí-lia, favorecendo um pior estímulo ao desenvolvimento das crianças. Tais associações foram diferentes com aquelas da maioria das pesquisas, onde as principais associações são: baixa renda familiar, baixa escolaridade materna e maior número de irmãos 23,24,27 .…”
Section: Discussionunclassified
“…The cognitive aspects evaluated include the development of seriation, classification, working memory and body schema. Although the instrument used is not a standardized test but a protocol of behavior observation, Performance Ratios (ID) were calculated as proposed in the literature 22 , i. e., the ID were calculated in percentage in each area, with maximum value of 100%. The indexes were calculated considering the number of assessed behaviors less the number of non-observed behaviors, multiplied by 100 and divided by the number of assessed behaviors 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding language evaluation, it was observed that the average of the communicative profile Performance Ratioswas high and similar in day care centers A and B, which indicates that in both day care centers, the children assessed have an appropriate language development and the children in both day care centers have similar communication profiles. A study done in Belo Horizonte with children aged between 2 and 6 years old of a publicday care center used the same instrument to assess language and also verified that children of this age group received high averages in all assessed aspects 18 . However, it is important to highlight that the referred study has a different scope to the present study and deals with profile comparison of anemic and non-anemic children.…”
mentioning
confidence: 76%
“…Records of the answers related to expected behaviors at each age were done on individual records, marking yes or no, respectively, according to the presence or absence of the item. Development indexes (DI) were used to qualify the children's answers 18 . The DI were calculated for each child, in each area, with a maximum value of 100%.…”
Section: Methodsmentioning
confidence: 99%